Infinite sums and products 4 (#13)

Calculus Level 3

1 1 2 2 + 1 3 2 1 4 2 + 1 5 2 = ? 1 - \frac {1}{2^2} + \frac {1}{3^2} - \frac {1}{4^2} + \frac {1}{5^2} - \cdots = \ ?

Give your answer to 2 decimal places.


The answer is 0.82.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Discussions for this problem are now closed

Emmanuel Lasker
Dec 31, 2014

n = 1 ( 1 ) n + 1 1 n 2 = n = 1 1 n 2 2 n = 1 1 ( 2 n ) 2 = \sum_{n=1}^{\infty}(-1)^{n+1}\frac{1}{n^2}=\sum_{n=1}^{\infty}\frac{1}{n^2}-2\sum_{n=1}^{\infty}\frac{1}{(2n)^2}= = n = 1 1 n 2 2 1 2 2 n = 1 1 n 2 = 1 2 n = 1 1 n 2 =\sum_{n=1}^{\infty}\frac{1}{n^2}-2\cdot\frac{1}{2^2}\sum_{n=1}^{\infty} \frac{1}{n^2}=\frac{1}{2}\sum_{n=1}^{\infty}\frac{1}{n^2} It's a well-known fact (see Basel Problem ) that ζ ( 2 ) = n = 1 1 n 2 = π 2 6 \zeta(2)=\sum_{n=1}^{\infty} \frac{1}{n^2}=\frac{\pi^2}{6} So the answer is 1 2 π 2 6 = 0.82... \frac{1}{2}\cdot \frac{\pi^2}{6}=\boxed{0.82...}

Notice that if we add 2 2 2 + 2 4 2 + 2 6 2 + \frac{2}{2^2}+\frac{2}{4^2}+\frac{2}{6^2}+\dots to the series,we get: ( 1 1 2 2 + 1 3 2 1 4 2 + ) + ( 2 2 2 + 2 4 2 + ) = 1 + 1 2 2 + 1 3 2 + \left(1-\frac{1}{2^2}+\frac{1}{3^2}-\frac{1}{4^2}+\dots\right)+\left(\frac{2}{2^2}+\frac{2}{4^2}+\dots\right)=1+\frac{1}{2^2}+\frac{1}{3^2}+\dots It is a well known fact that 1 + 1 2 2 + 1 3 2 + = π 2 6 1+\frac{1}{2^2}+\frac{1}{3^2}+\dots=\frac{\pi^2}{6} .Also note that: 2 2 2 + 2 4 2 + = 2 ( 1 2 2 + 1 4 2 + ) = 2 × 1 2 2 ( 1 + 1 2 2 + 1 3 2 + ) = 1 2 × π 2 6 = π 2 12 \frac{2}{2^2}+\frac{2}{4^2}+\dots=2\left(\frac{1}{2^2}+\frac{1}{4^2}+\dots\right)\\=2\times\frac{1}{2^2}\left(1+\frac{1}{2^2}+\frac{1}{3^2}+\dots\right)\\=\frac{1}{2}\times\frac{\pi^2}{6}=\frac{\pi^2}{12} Let 1 1 2 2 + 1 3 2 + = x 1-\frac{1}{2^2}+\frac{1}{3^2}+\dots=x then the abovementioned process can be written as: x + π 2 12 = π 2 6 x = π 2 6 π 2 12 = π 2 12 = 0.82 t o 2 d . p x+\frac{\pi^2}{12}=\frac{\pi^2}{6}\\x=\frac{\pi^2}{6}-\frac{\pi^2}{12}=\frac{\pi^2}{12}=\boxed{0.82}\;to\;2\;d.p

Jake Lai
Dec 31, 2014

By the Weierstrass factorization theorem , we rewrite sin x x \frac{\sin x}{x} in terms of its roots x = n π x = n\pi for n Z { 0 } n \in \mathbb{Z} \setminus \lbrace 0 \rbrace :

sin x x = ( m = 1 ( 1 + x m π ) ) ( n = 1 ( 1 x n π ) ) = n = 1 ( 1 x 2 n 2 π 2 ) \frac{\sin x}{x} = \Bigg(\prod_{m=1}^{\infty} (1+\frac{x}{m\pi})\Bigg) \Bigg(\prod_{n=1}^{\infty} (1-\frac{x}{n\pi})\Bigg) = \prod_{n=1}^{\infty} (1-\frac{x^{2}}{n^{2}\pi^{2}})

Using Newton's sums to collect the x 2 x^{2} terms, we see that the coefficient is 1 π 2 k = 1 1 k 2 \displaystyle -\frac{1}{\pi^{2}} \sum_{k=1}^{\infty} \frac{1}{k^{2}} .

The Taylor series of sin x \sin x is k = 1 ( 1 ) k x 2 k + 1 ( 2 k + 1 ) ! \displaystyle \sum_{k=1}^{\infty} \frac{(-1)^{k}x^{2k+1}}{(2k+1)!} . From this, we then know sin x x = k = 1 ( 1 ) k x 2 k ( 2 k + 1 ) ! \displaystyle \frac{\sin x}{x} = \sum_{k=1}^{\infty} \frac{(-1)^{k}x^{2k}}{(2k+1)!} .

The coefficient here of x 2 x^{2} , then, is 1 6 -\frac{1}{6} . Equating the two coefficients and rearranging yields

k = 1 1 k 2 = π 2 6 \sum_{k=1}^{\infty} \frac{1}{k^{2}} = \frac{\pi^{2}}{6}

Multiplying both sides by 1 1 2 = 1 2 1-\frac{1}{2} = \frac{1}{2} , we get

k = 1 1 k 2 2 ( 2 k ) 2 = k = 1 ( 1 ) k k 2 = π 2 12 \sum_{k=1}^{\infty} \frac{1}{k^{2}}-\frac{2}{(2k)^{2}} = \sum_{k=1}^{\infty} \frac{(-1)^{k}}{k^{2}} = \boxed{\frac{\pi^{2}}{12}}

Very nice , just 14 and have very good ability

U Z - 6 years, 5 months ago

Not really, I'm just really interested in real/complex analysis.

Jake Lai - 6 years, 5 months ago

That definitely is having very good ability, how do you study real/complex analysis by yourself?

찬홍 민 - 6 years, 3 months ago

First of all, observe that

n = 1 1 ( 2 n ) 2 = 1 4 ζ ( 2 ) \sum_{n=1}^{\infty} \frac{1}{(2n)^{2}} = \frac{1}{4} \zeta(2)

and

n = 1 1 ( 2 n 1 ) 2 = ζ ( 2 ) n = 1 1 ( 2 n ) 2 = ζ ( 2 ) 1 4 ζ ( 2 ) = 3 4 ζ ( 2 ) \sum_{n=1}^{\infty} \frac{1}{(2n-1)^{2}} = \zeta(2) - \sum_{n=1}^{\infty} \frac{1}{(2n)^{2}} = \zeta(2) - \frac{1}{4} \zeta(2) = \frac{3}{4} \zeta(2)

Then also observe that the sum we want may be written as

n = 1 1 ( 2 n 1 ) 2 n = 1 1 ( 2 n ) 2 = 3 4 ζ ( 2 ) 1 4 ζ ( 2 ) = 1 2 ζ ( 2 ) = π 2 12 0.82 \sum_{n=1}^{\infty} \frac{1}{(2n-1)^{2}} - \sum_{n=1}^{\infty} \frac{1}{(2n)^{2}} = \frac{3}{4} \zeta(2) - \frac{1}{4} \zeta(2) = \frac{1}{2} \zeta(2) = \frac{\pi^{2}}{12} \approx 0.82

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...